A NEW METHOD FOR IDENTIFYING SEISMICITY PERIODICITIES - Lyubushin A.A.,Jr.; Pisarenko V.F.; Ruzhich V.V.; Buddo V.Y. (My University, 1998)
A new technique of spectral analysis is proposed to deal with point processes such as earthquakes, volcanic eruptions, etc. The technique is based on the maximum likelihood estimation of spectral parameters of the point process and can be used to analyze catalogs with variable lower levels of complete reporting, as well as catalogs of historical earthquakes. The technique was used in this study to identify periodicities in the 1725-1996 Baikal seismicity and the worldwide catalog for 1900-1995. The Baikal periodicities are 2.5, 5, 10-11, 18-19, and 35-50 years, the periods for the worldwide catalog being 1.5, 4, 9-10, and 35-40 years. Possible causes of these periodicities are discussed.